LEGAL STATUS OF RELIGIOUS ORGANILEGAL STATUS OF RELIGIOUS ORGANIZATIONSZATIONS (Revista Inclusiones, 2019)
Within the context of reforming civil legislation and legislation on freedom of religion and the development of pluralism of opinions regarding the role of subjects of religious worship in a secular state, the issues of the content and structure of the legal status of religious organizations and their relationships with other participants in civil relations are of particular relevance. However, these issues cannot be resolved without a clear understanding of the status of religious organizations in the Russian Federation.